2022
DOI: 10.3389/fpsyg.2022.842138
|View full text |Cite
|
Sign up to set email alerts
|

Influence Mechanism of Social Support of Online Travel Platform on Customer Citizenship Behavior

Abstract: Customer citizenship behavior has attracted widespread attention from scholars due to its capacity of enabling enterprises to gain competitive advantages of low costs and high efficiency by giving full play to the initiative of customers. Based on the S-O-R Model, we have established the theoretical model to study the influence imposed by social support of online travel platform enterprises on customer citizenship behavior against the backdrop of the sharing economy. This research tests the fitting of the theo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 49 publications
1
7
0
Order By: Relevance
“…In terms of cognition, Lemon and Verhoef (2016) attempted to combine consumer experience with behavior in terms of consumer satisfaction and service quality and found that consumer experience has a positive impact on behavioral intention. In terms of affection, Ning and Hu (2022) confirmed that affective information triggers emotional responses and then influences consumers’ behavioral intention. During the Double 11 period, when consumers have cognitive experience from information, they might participate in Double 11 to buy products even beyond their budget.…”
Section: Research Model and Hypothesesmentioning
confidence: 67%
“…In terms of cognition, Lemon and Verhoef (2016) attempted to combine consumer experience with behavior in terms of consumer satisfaction and service quality and found that consumer experience has a positive impact on behavioral intention. In terms of affection, Ning and Hu (2022) confirmed that affective information triggers emotional responses and then influences consumers’ behavioral intention. During the Double 11 period, when consumers have cognitive experience from information, they might participate in Double 11 to buy products even beyond their budget.…”
Section: Research Model and Hypothesesmentioning
confidence: 67%
“…Crocker and Canevello (2008) demonstrated the perceived support from others leads people to reciprocate with similar supportive behaviours. In accordance with social exchange theory, customers exhibit positive behaviours when they believe that businesses offer good social support during the consumption process (Ning & Hu, 2022). Similarly, theories of organisational climate and social support predict that supportive climates enhance customer voluntary behaviours (Liao et al, 2022;Schneider, 1990), and Ning and Hu (2022) demonstrate that social support has a significant effect on consumer citizenship behaviour.…”
Section: Cps and Ccbsmentioning
confidence: 78%
“…Second, whereas in the context of employment there is conceptual awareness of the role of perceived support in the relationship between PPJ and organisational citizenship behaviour (Dominic et al, 2021;Moorman et al, 1998), no empirical studies in the marketing literature have investigated the role of customer perceived support (CPS) in the PPJ-CCBs relationship. Recent research has shown that CPS is positively impacted by overall CPJ (Choi & Lotz, 2018), and CPS is considered a vital antecedent of customer voluntary performance (i.e., citizenship behaviours) (Bettencourt & Brown, 1997;Ning & Hu, 2022;Rosenbaum & Massiah, 2007), which implies a possible mediating effect of CPS in the PPJ-CCBs relationship-an effect that has not yet been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…However, this assertion remains speculative, necessitating further research to validate its accuracy. Additionally, future investigations should broaden their scope to encompass a diverse range of scenarios, exploring specific contexts influencing residents' motivation for citizenship behaviors, including online social environments [79] and the impact of citizenship behaviors of others [22,80], to deepen the understanding of the interplay between altruism and egoism in tourism research.…”
Section: Limitationsmentioning
confidence: 99%